2013
DOI: 10.1002/ece3.421
|View full text |Cite
|
Sign up to set email alerts
|

Multiple evolutionary processes drive the patterns of genetic differentiation in a forest tree species complex

Abstract: Forest trees frequently form species complexes, complicating taxonomic classification and gene pool management. This is certainly the case in Eucalyptus, and well exemplified by the Eucalyptus globulus complex. This ecologically and economically significant complex comprises four taxa (sspp. bicostata, globulus, maidenii, pseudoglobulus) that are geographically and morphologically distinct, but linked by extensive “intergrade” populations. To resolve their genetic affinities, nine microsatellites were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 95 publications
5
33
0
Order By: Relevance
“…The E. globulus from the Strzelecki Ranges is genetically differentiated from the more coastal populations in the Otway Ranges and islands of the Furneaux group (Jones et al 2013) and is the most drought tolerant of the E. globulus races (Strzelecki>Furneaux>Western Otways; (Dutkowski and Potts 2012)). The ranking of the races in terms of their tolerance to germination at high temperatures (Strzelecki>Western Otways>Furneaux; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The E. globulus from the Strzelecki Ranges is genetically differentiated from the more coastal populations in the Otway Ranges and islands of the Furneaux group (Jones et al 2013) and is the most drought tolerant of the E. globulus races (Strzelecki>Furneaux>Western Otways; (Dutkowski and Potts 2012)). The ranking of the races in terms of their tolerance to germination at high temperatures (Strzelecki>Western Otways>Furneaux; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This required sufficient differentiation in International Journal of Forestry Research allele frequencies so that individuals with genotypes that are admixed between two species could be detected. Yet, the level of differentiation between species estimated from the inbreeding coefficient ST is low in comparison to a range of other eucalypts [63][64][65][66], particularly considering that the comparison is between taxonomically distinct species. However, because the range-wide sampling strategy used here covered geographically discrete populations of these widespread species (Figure 1), it probably captures significant within species differentiation, which could subsequently reduce ST values between species [67][68][69][70].…”
Section: Performance Of the Approachmentioning
confidence: 99%
“…Indeed, Vucetich and Waite (2003) have shown that peripheral populations can experience up to 30 times greater genetic drift than central-core populations. Although peripheral populations have traditionally been studied in relation to a continuous central core (Eckert et al 2008;Jones et al 2013), in the case of E. cordata, the cores are not continuous but have become recently fragmented. This hypothesis is supported by the low differentiation between populations within the 'phantom core', which is suggestive of a more continuous distribution in the cores in the recent past.…”
Section: Discussionmentioning
confidence: 99%
“…The microsatellite and chloroplast markers were chosen so that the results of this study could be compared with previous works (McKinnon et al 2004b;Jones et al 2005Jones et al , 2013Rathbone et al 2007). We used DArT markers, which have wide genome coverage Steane et al 2011), so as to achieve high resolution for the phylogenetic component of the study.…”
Section: Introductionmentioning
confidence: 99%